Transvaginal ultrasonography in first trimester of pregnancy and its comparison with transabdominal ultrasonography - Aneet Kaur; Amarjit Kaur (Wolters Kluwer Medknow Publications, 2011)
Objectives : Examination of pregnant women in the first trimester with transvaginal ultrasonography with the aim to study various fetal development markers, e.g., gestation sac, yolk sac, fetal heart motion, CRL length, and fetal anatomy in both normal and abnormal pregnancies. Comparative evaluation of transvaginal ultrasonography vis-ΰ-vis transabdominal scanning in the study of first trimester of pregnancy and its complications. To assess the relative merits and demerits of transvaginal ultrasonography in comparison with the transabdominal technique. Materials and Methods : The study will be conducted on 50 females patients during the first trimester of pregnancy. The study population will consist of both normal and abnormal pregnancies. These patients will be included on the basis of suspicion of or proven pregnancy of duration up to 12 weeks from LMP. The evaluation of the patients will include the following: Record of patients obstetrical history and clinical examination, record of pregnancy test and relevant investigations, ultrasonic examination of pregnancy. (a) Transabdominal ultrasound scanning will be done with moderately distended bladder by using real time scanners with low frequency probe (3/3.5 MHz); (b) transvaginal sonography will be done with the real-time sector scanner using high-frequency endovaginal probe (5/7.5 MHz), after the patient voids urine. Relevant images will be taken by using the multiformat automatic camera. Results and Conclusions : In the study of 46 normal intrauterine pregnancies, TVS showed additional information in 36 patients (78.3%) as compared to TAS, in detection of gestation sac, yolk sac, double bleb sign, or better visualization of embryonic anatomy. In the abnormal pregnancy (n=17), TVS provided more information in 11 cases (64.9%), which included detection of embryonic demise, yolk sac, double bleb sign, or subchorionic hemorrhage. Regarding ectopic gestations (n=7), TVS gave additional information in 5 cases (71.4%) which included detection of ectopic fetal pole, yolk sac, decidual cast, adnexal mass, and fluid in cul de sac. In two cases, both TAS and TVS gave equal information. However, in 2 cases TAS demonstrated the extent of intraabdominal fluid better than TVS. The other advantages of TVS over TAS are that there is no need for the patient to have uncomfortably full bladder and time is saved from having to wait for bladder to fill. Thus, the potential preoperative patient can be kept fasting. TVS is also superior in obese patients, in patients with retroverted uterus and it also bypasses obstacles such as bone, gas filled bowel, and extensive pelvic adhesions. The limitations encountered with TVS were limited manoveuribility of probe and because of the unorthodox position and angle of the transducer, correct orientation was difficult initially.